DIGITAL TRANSFORMATION OF CHINA’S SPORTS INDUSTRY AND ITS ALIGNMENT WITH WTO E-COMMERCE NEGOTIATIONS: AN INSTITUTIONAL PERSPECTIVE - Bi, Chenchao; Choon Lian, Denise Koh (Veredas do Direito, 2026)
This research critically analyzes the digital transformation of the Chinese sports industry within the institutional context of its conformity with the WTO e-commerce regulations. The study focuses on emerging innovations such as e-sports, digital media platforms and artificial intelligence which have contributed to the rapid growth and engagement of the digital economy. Through a systematic literature review of 34 peer-reviewed sources published in the period 2018-2024, this paper looks at the interactions of China's regulatory regime within the international trade regime. Findings show areas of convergence, such as digital intellectual property protection and the use of AI in sports services, and clear divergences around data localisation and digital sovereignty. In addition, some regulatory gaps may affect China's international expansion of digital sports platforms, even if the market is robust. The paper concludes with policy recommendations to improve cross-border data flow governance, harmonize national regulations with WTO principles, and enhance China’s global competitiveness in digital sports. Overall, the study provides industry-specific insights into regulatory coherence and its impact on international digital trade participation.